Self-protection as a limit to strategic delegation in the context of global pollution problems - Clemens Heuson (Helmholtz-Zentrum für Umweltforschung (UFZ), 2013)
This paper analyses the outcome of non-cooperative national efforts in combatting global pollu-tion problems when governments are elected by their citizens. It is well-known that the latter tend to vote governments that are less 'green' than the median voter in order to commit to lower national mitigation efforts, which further increases the inefficiently high amount of global emis-sions. However, the present paper shows that the option of self-protection against environmen-tal damages, which has been invariably neglected in the relevant literature to date, alleviates or even completely offsets such strategic delegation and the related adverse effects.
Keywords: C72; D72; H41; Q58; 330; strategic delegation; global pollution problems; self-protection; non-cooperative behaviour